RELATIONSHIP BETWEEN THE GOLDBERG SPECTRUM AND THE B-FREDHOLM SPECTRA - MESSIRDI, B; BENHARRAT, M (My University, 2017)
A classical result of J. Ph. Labrousse (Rev. Roumaine Math. Pures Appl. 25, 1391-1394, 1980) concerning the symmetric difference between the essential quasi-Fredholm spectrum and the Goldberg spectrum of closed operators in Hilbert spaces is extended to the case of B-Fredholm spectra. The obtained results are used to describe the essential spectrum and some B-Fredholm spectra of some transport operators.
Keywords: B-Fredholm operators; Quasi-Fredholm operators; Essential qausi-Fredholm spectrum; B-Fredholm spectrum; Transport operator